Method for preparing electrocatalysts with ultra‐high activity using graphene oxide as the support. (1st August 2014) - Hu, Zhongliang; Jiang, Haiyun; Zhao, Xuehui; Zhang, Wei; Li, Na
Abstract : A novel method has been developed to prepare efficient electrocatalysts for methanol oxidation using graphene oxide (GO) as the support, and the deposited Pt–Ru particles on the sheets of GO are very thin nanoplatelets. The method mainly includes the following steps: Pb 2+ adsorption on the sheets of GO, Pb 2+ electrochemical reduction and galvanic displacement of Pb 0 by Pt 2+ and Ru 3+ . The prepared catalyst displays a large electrochemically active surface area and its mass electrocatalytic activity towards methanol oxidation reaction is about 15 times higher than that of commercial catalysts. The presented results demonstrate that this developed method could be viable for solving the problem of low electrocatalytic activity in direct methanol fuel cell anodes.